2007
DOI: 10.18553/jmcp.2007.13.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Resource Utilization of Adding Salmeterol in Combination or Separately to Inhaled Corticosteroids

Abstract: BACKGROUND: The addition of a long-acting beta-agonist (LABA) to an inhaled corticosteroid (ICS) for patients with moderate or severe persistent asthma improves outcomes such as pulmonary function, reduces exacerbations requiring oral steroids, and reduces use of rescue beta-agonists.OBJECTIVE: To assess the key resource utilization outcomes of adding salmeterol, a LABA, to fluticasone, an ICS, either as a fixed-combination inhaler (fluticasone-salmeterol [FSA] or as a separate inhaler used concomitantly with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 22 publications
0
17
1
Order By: Relevance
“…29 In another retrospective study using administrative data, the addition of LABA therapy to existing ICS treatment appeared to improve asthma outcomes. 30 These authors also found adherence to be significantly better for the ICS/LABA combination preparation when compared to separate inhalers for ICS and LABA. Importantly, our study accounts for patient use or adherence such that we calculate the effect of therapy in only those with apparently consistent use.…”
Section: Discussionmentioning
confidence: 94%
“…29 In another retrospective study using administrative data, the addition of LABA therapy to existing ICS treatment appeared to improve asthma outcomes. 30 These authors also found adherence to be significantly better for the ICS/LABA combination preparation when compared to separate inhalers for ICS and LABA. Importantly, our study accounts for patient use or adherence such that we calculate the effect of therapy in only those with apparently consistent use.…”
Section: Discussionmentioning
confidence: 94%
“…Data on adherence (including compliance and persistence) were reported in non-randomized observational and RCTs in asthma (n=8 [17][18][19][20][21][22][23][24] and n=4, [25][26][27][28] respectively) and COPD (n=2 29,30 and n=2, 31,32 respectively; Table 1). Adherence was assessed as medication usage (including self-reported), [25][26][27]32 prescription/refill rates, [17][18][19]21 MPR, 18,20 treatment days, 17,18 treatment persistence/ interruptions, 19,[22][23][24][28][29][30] and residual treatment. 31…”
Section: Adherence Outcomesmentioning
confidence: 99%
“…Prescription/Refill Rates Results from four retrospective studies in asthma (patient numbers ranging from 2426 to 5118) indicated that users of single inhalers filled significantly more prescriptions than users of multiple inhalers over time periods of 6 21 and 12 months [17][18][19] (all P<0.05; Table 1). Using medical and pharmacy claims data from the Ingenix database collected between April 2001 and July 2001, prescriptions for single inhalers were significantly higher than the number of requests for ICS in the multiple-inhalers group (4.06 versus 2.35; P<0.001).…”
Section: Evidence From Non-randomized Observational Studiesmentioning
confidence: 99%
“…The reasons for the increased use of fixed-dose combination of LABA and ICS are said to be the ease of use and better adherence14 3033 and better asthma control 21 3235…”
Section: Discussionmentioning
confidence: 99%